Energy dependence of processing and breakdown properties of Cu and Mo - H. Timko; M. Aicheler; P. Alknes; S. Calatroni; A. Oltedal; A. Toerklep; M. Taborelli; W. Wuensch; F. Djurabekova; K. Nordlund (Physical Review Special Topics. Accelerators and Beams, 2011)
Obtaining basic knowledge of breakdowns is desirable in many fields of physics; however, often the energy absorbed by a breakdown is not known or can vary by large amounts. We have therefore investigated how processing and breakdown properties scale with available energy for two materials, Cu and Mo, in the energy range of about 1 mJ to 1 J. A central result obtained is that there appears to be an optimum energy for processing and thus the highest possible electric field a processed material can sustain without breaking down depends on energy accordingly; what this implies for radio frequency cavity processing is discussed as well. For Cu, both the local field and the field enhancement factor showed only a weak dependence on energy; the average of the local field over the entire energy range investigated was (9.6±0.4)  GV/m at breakdown. For Mo, the local field increased with increasing energy, while the field enhancement factor remained constant at 34±2. Finally, a possible explanation of the direct current (DC) processing mechanism—at least in the case of Mo—as an oxide removal process is presented.